Beauty, Underage Drinking, and Adolescent Risky Behaviours - Colin P. Green; Luke B. Wilson; Anwen Zhang (Global Labor Organization (GLO), 2023)
Physically attractive individuals experience a range of advantages in adulthood including higher earnings; yet, how attractiveness influences earlier consequential decisions is not well understood. This paper estimates the effect of attractiveness on engagement in risky behaviours in adolescence. We find marked effects across a range of risky behaviours with notable contrasts. Attractive adolescents are more likely to engage in drinking; the gap between attractive and unattractive adolescents in terms of propensity to drink constitutes about one fifth of the baseline mean. In contrast, more attractive adolescents are less likely to smoke, use drugs, or practice unprotected sex. Investigation into the underlying channels reveals that physically attractive adolescents are more popular, have higher self-esteem and personality attractiveness. Popularity leads to a higher likelihood of engagement in "cool" risky behaviours and a lower likelihood for "uncool" behaviours, while self-esteem and personality generally predict a lower likelihood in engaging in all risky behaviours. Our findings suggest physical attractiveness in adolescence carries long-lasting consequences over the life course.
Keywords: I12; J10; 330; beauty; risky behaviours; adolescent development